Generation and analysis of 5G downlink signal - Parveen, Nagma; Abdullah, Khaizuran; Badron, Khairayu; Abdul Rahman, Farah Diyana; Morshidi, Malik Arman (Penerbit Akademia Baru, 2022)
The evolution of wireless communication technology has provided a viable important concept for the next-generation wireless mechanism. The technology may provide a variety of services for different terminals, such as voice and multimedia data services through a mobile phone, as well as improved packet delivery across cellular networks. Fifth Generation (5G) New Radio (NR) is the most recent radio air interface designed for next-generation wireless communication networks to fulfill the increasing needs of connected devices. It is built to enable a variety of situations, including increased large machine-to-machine communications, mobile broadband, and ultra-reliable low-latency communications. The objective of the study is to generate and analysis the 5G signal. The evolution of wireless communication generation with its advantages, disadvantages and their features are explained and discussed. The requirements of 5G are discussed. The 5G NR signal is generated and analyzed using the various parameters in the waveform generator app in MATLAB. The downlink scenario is considered. The time scope and spectrum analyzer graph of 5G NR signal is discussed. The modulation used here for the generation of 5G signal is 16 QAM modulation and 64 QAM modulation techniques.